2016
DOI: 10.21307/ane-2017-001
|View full text |Cite
|
Sign up to set email alerts
|

Lithium – therapeutic tool endowed with multiple beneficiary effects caused by multiple mechanisms

Abstract: Mood disorders are relatively common serious human diseases for which there is often no ideal pharmacotherapy. Basic characteristic of these diseases is affective disorder shifting the mood of the patient to depression (together with anxiety or not) or towards to euphoria. Available drugs are usually divided into two groups -mood stabilizers, which are used primarily to treat bipolar disorder, and antidepressants for the treatment of unipolar depression. Lithium is still recommended as the first choice for dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 194 publications
(281 reference statements)
0
42
0
3
Order By: Relevance
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Safe therapeutic concentrations of lithium are typically below 1 mol/L in these patients (Geddes and Miklowitz, 2013; Yatham et al, 2013; Mohammad and Osser, 2014). In preclinical and clinical research, lithium was recognized for robust neuroprotective effects regarding various pathologic conditions (Vo et al, 2015; Doeppner et al, 2016; Vosahlikova and Svoboda, 2016). Recent studies have also identified protective effects of lithium in cardiovascular and cerebrovascular diseases (Gold et al, 2011; Chiu and Chuang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Транспорт лития через клеточные мембраны. Литий может входить в клетку несколькими способами, наиболее частый -пассивный транспорт через потенциал-зависимые (voltage-gated class) и потенциал-независимые натриевые каналы (non-voltage-gated epithelial class) [20,36,45]. Проницаемость потенциал-зависимых натриевых каналов примерно одинакова для ионов Na + и Li + [45].…”
unclassified
“…Литий может входить в клетку несколькими способами, наиболее частый -пассивный транспорт через потенциал-зависимые (voltage-gated class) и потенциал-независимые натриевые каналы (non-voltage-gated epithelial class) [20,36,45]. Проницаемость потенциал-зависимых натриевых каналов примерно одинакова для ионов Na + и Li + [45]. При этом ионный радиус негидратированного лития (0,68 Å) близок к размеру негидратированного магния (0,65 Å), что объясняет конкуренцию между этими ионами в Mg 2+ -зависимых ферментах и опосредует основные биологические эффекты лития [7,13,31,45].…”
unclassified
“…In addition to those natural products, the salt ionic compound, Lithium chloride, is also known to be beneficial. It is currently used in the treatment for bipolar disorder (Vosahlikova and Svoboda, 2016) and has been shown to increase lifespan of C. elegans (McColl et al, 2008). Lithium chloride has even been correlated with longevity in humans (Zarse et al, 2011).…”
Section: Pharmacological Studies Of Agingmentioning
confidence: 99%